Penggunaan Aplikasi Artificial Intelligence (AI) sebagai Alat Bantu Penyelesaian Tugas Akademik pada Mahasiswa Perpustakaan dan llmu Informasi Universitas Negeri Padang Angkatan 2023 - Agustin, Vanya; Marlini, Marlini (Jurnal Ragam Pengabdian, 2026)
The rapid development of digital technology in higher education has encouraged the increasing use of Artificial Intelligence (AI) applications as tools to support academic activities among university students. The purpose of this study is to analyze the use of Artificial Intelligence (AI) applications as tools for completing academic assignments among students of the Library and Information Science Program at Universitas Negeri Padang class of 2023. This study employed a descriptive quantitative method with a population of 75 active students selected using a total sampling technique. Data were collected through questionnaires based on the Technology Acceptance Model (TAM) and the Ellis information-seeking behavior model, which include perceived usefulness, perceived ease of use, starting, chaining, browsing, differentiating, monitoring, extracting, verifying, and ending. Data analysis was conducted using mean score calculations with the assistance of SPSS 26.0. The results show that the overall use of AI applications obtained a mean score of 3.21, which falls into the high category. Several sub-indicators, such as adjustment to goals (3.28), suitability for purpose (3.26), and clarity of conclusions (3.32), were categorized as very high. These findings indicate that students perceive AI as beneficial in improving academic performance, increasing productivity, facilitating information retrieval, and supporting the completion of academic assignments more effectively and systematically. However, students still need to strengthen critical thinking skills and verify the validity and credibility of information generated by AI to ensure academic responsibility. This study contributes to understanding students’ behavior in utilizing AI technology within academic environments and may serve as a reference for developing digital literacy and ethical AI usage in higher education.